PENGGUNAAN MEDIA SOSIAL WHATSAPP PADA PEMBELAJARAN DARING DI KELAS I SDN 25 INDRALAYA - Anjarria Lestari Sari; Hasmalena Hasmalena; Laihat Laihat (Universitas Sriwijaya, 2021)
This study has the following objectives To describe the application online learning using whatsApp social media for students. The type of research used is descriptive quantitative research. The study was conducted in February 2021. The sample in this study are teacher and students of grade I SDN 25 Indralaya. Data collection using a questionnaire and observation sheet. Data analysis techniques on this research uses descriptive statistical techniques. The results showed that the effectiveness of the use of social media whatsApp for online learning in grade I SDN 25 Indralaya classified as moderate with a percentage of 35%. Meanwhile, from the results of observations shows that the use of whtasApp social media on learning online in class I was classified as good with a percentage of 44%. Keyword: effectiveness, whatsApp Social media, online learning